REBOA (Resuscitative Endovascular Balloon Occlusion of the Aorta): Brauchen wir das wirklich? - Wortmann, Markus; Böckler, Dittmar (Notfall & Rettungsmedizin, 2019)
Background: Non-compressible torso hemorrhage (NCTH) continues to be one of the major causes of death, both in military and civilian trauma patients. Objective: Explanation of the REBOA (Resuscitative Endovascular Balloon Occlusion of the Aorta) technique, potential fields of application, potential complications, relevance in daily emergency medicine. Material and method: Description of previous areas of REBOA application, evaluation of current trauma surgical literature, discussion regarding the practical utilization. Results: During the REBOA procedure, a transfemoral balloon catheter is placed into the aorta to establish inflow control and maintain blood pressure until permanent hemostasis is achieved. The current trauma surgical literature shows that REBOA is successfully able to improve both the systolic blood pressure and the mean arterial pressure, and reduce the heart rate in most of the cases. However, there is still no valid evidence for a reduction in hemorrhage-associated mortality. Conclusions: Due to potential vascular complications of REBOA, endovascular expertise is indispensable; in addition, given the small numbers of cases, both the initial and continued training are important. Nevertheless, REBOA represents a potentially life-saving tool that should be part of the armamentarium of any large trauma center.
First Online: 02 January 2018
Gesehen am 31.05.2019